Stili vocali e coreutici nella ricerca di Alan Lomax: Cantometrics, Choreometrics ed equità culturale (De Musica, 2022)
In this essay we want to analyze the distinctive features of the system theorized by Lomax, focusing in particular on the facsimile of one of the coding sheets on which, among other things, the place where the recording was noted was consumed, the language used by the performers, the sound source and how many members took part in the performances. A brief foray of a theoretical nature is made, secondly, on Choreometrics, the other classification system formulated by the ethnomusicologist and based on research carried out by the Hungarian choreographer and theorist of dance Rudolf Von Laban.
Keywords: Ethnomusicology; Ethnology; Anthropology; Alan Lomax; Cantometrics; Choreometrics; Rudolf Von Laban